Role Orientations and Audience Metrics in Newsrooms: An Examination of Journalistic Perceptions and their Drivers. Issue 3 (15th March 2020) - Belair-Gagnon, Valerie; Zamith, Rodrigo; Holton, Avery E.
Abstract: This survey of journalists, editors, and managers working for news organizations in the United States explores the perceived importance of citizen and consumer role orientations among newsworkers. It then examines how useful these professionals perceive particular audience metrics to be in fulfilling those roles orientations. This examination takes into account the contextual factors that may influence those perceptions at the individual and organizational levels. We find that newsworkers perceive some audience metrics more useful than others and generally perceive them to be more useful for helping them enact a consumer role orientation that has been historically deemed to be of lesser import. However, these perceptions vary across organizational contexts, and particularly according to the newsworker's position within an editorial hierarchy. These findings contribute to the literatures that argue that quantified audiences are an important part of role orientation formation.